Physiological difficult airway management in the emergency department - Ghaffar, Sara; Waheed, Shahan (Journal of the Pakistan Medical Association, 2026)
The current study was planned to discuss the importance of endotracheal intubation in airway management, focusing on the less explored concept of physiologically difficult airways in patients with unstable physiological states. Addressing three key physiological challenges is central to successful airway management. These are: refractory hypoxia, refractory hypotension, and metabolic acidosis. Refractory hypoxia occurs when individuals are unable to sustain sufficient oxygen saturation levels even with the administration of high-flow oxygen. Interventions include proper patient positioning, using positive end expiratory pressure through non-invasive positive pressure ventilation, and inhaled pulmonary vasodilators. Refractory hypotension is defined as low blood pressure despite adequate fluid resuscitation or vasopressor support. Strategies include aggressive volume resuscitation, initiating norepinephrine infusions, preparing for peripherally administered vasopressor boluses, and using diluted phenylephrine when blood pressure drops post-intubation. Metabolic acidosis relates to severe acid-base disturbances that increase the risk of complications during intubation. Intubation should be avoided when possible, and a short trial of non-invasive positive pressure ventilation may help support respiratory work. For awake intubations, topical anaesthesia is crucial. Implementation of a difficult physiological airway algorithm as part of a quality initiative is critical, with a focus on simulation-based training. The algorithm incorporates anatomical and physiological predictors of difficult airways to empower emergency physicians to make timely interventions and prevent adverse outcomes. Recognising and addressing physiological challenges during intubation is essential in critically ill patients presenting to the emergency department. Key Words: Difficult airway, Physiological difficult airway, Refractory hypoxia, Refractory hypotension, Metabolic acidosis, Emergency intubations.